Rituals of the Past : Prehispanic and Colonial Case Studies in Andean Archaeology - Bautista, Stefanie L.; Rosenfeld, Silvana A. (Book collections on Project MUSE., 2017)
"Explores various methods archaeologists use to identify ritual in the material record and discusses the influence it had on the formation, reproduction, and transformation of community in past Andean societies. How ritual influenced, permeated, and altered political authority, economic production, shamanic practice, and landscape cognition over 3,000 years"--Provided by publisher.